1998
DOI: 10.1119/1.879933
|View full text |Cite
|
Sign up to set email alerts
|

Do they stay fixed?

Abstract: We report the results of a longitudinal study of three nonmajor introductory classes that achieved relatively high FCI gains (g=1.5) using an inquiry-based tutorial approach. Original FCI gains persisted as many as four years following instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 0 publications
4
23
0
1
Order By: Relevance
“…There have been a few studies [4][5][6][7][8], most quite recent, suggesting that conceptual knowledge in physics may be retained better than the primarily factual knowledge measured in retention studies such as Ref. [3].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There have been a few studies [4][5][6][7][8], most quite recent, suggesting that conceptual knowledge in physics may be retained better than the primarily factual knowledge measured in retention studies such as Ref. [3].…”
Section: Introductionmentioning
confidence: 97%
“…An early study by Francis et al [4] showed little drop in scores on the Force Concept Inventory after some years for a self-selected set of volunteers. It is unknown how much the volunteers may have reencountered the material during the retention interval, and the absence of uncertainties or standard deviations for the sample populations in the publication prevent quantitative conclusions.…”
Section: Introductionmentioning
confidence: 98%
“…A second group (with learners labeled 2,5,7,9,10,14,16,21,23,25,26,29), characterized by an initial (postinstruction) similarity index lower than 0.6 with respect to the ex-type, has further lowered these values by increasing the similarity towards the de-type profile. A final group (with students labeled 3, 4,8,18,20,27,28), all starting with ex-type similarities higher than 0.6, after four years, essentially remained with the same similarities with respect to the three typologies.…”
Section: Resultsmentioning
confidence: 99%
“…Here, for the first time to the best of our knowledge, a quantitative analysis about the long term stability of student strengthening of reasoning skills for everyday problem solving in thermal science is presented. Only two previous studies attempted to address this issue some time ago by investigating the long term learning effects of "active engagement" methods in mechanics courses at university, providing promising results about the achievement of permanent change in students' conceptual framework up to three years after instruction [28,29]. We invited the same students from the first studynow mostly graduated professionals-to answer the same questionnaire they answered four years ago in the researchlike context of the "Mission to Mars" OI-based workshop.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of retention on other standardized instruments testing conceptual physics knowledge [9][10][11][12] show little or no loss of knowledge over retention intervals ranging from several months to several years. Indeed, this is consistent with our finding that the average score on the MBT among the retest participants is remarkably stable over the interval from the completion of freshman mechanics to graduation.…”
Section: Conclusion a Quantitative Findingsmentioning
confidence: 99%